Nebria (Boreonebria) nivalis ... - Sundukov, Yurii N.; Novomodnyi, Evgeniy V. (Zenodo, 2022)
Nebria (Boreonebria) nivalis (Paykull, 1790) Material. Verkhne-Bureinsky Distr., upper reaches of the Umalta River, pass on the Niman River, Dedovich’s hut, 7.07.2003, E. Novomodnyi leg., 1♂. Distribution. A boreal Holarctic species. In the Palearctic: from the British Isles in the west to Chukotka, Kamchatka, and the Northern Kuril Islands in the east, from the Arctic coast in the north to the south of the Scandinavian Peninsula, the Middle Urals, Altai, Mongolia, the north of Primorsky Region, and Central Sakhalin in the south. ... : Published as part of Sundukov, Yurii N. & Novomodnyi, Evgeniy V., 2022, Ground beetles (Coleoptera, Carabidae) of Khabarovsky Region in the collection of Grodekov Khabarovsk Regional Museum, pp. 570-593 in Amurian Zoological Journal XIV (4) on page 572, DOI: 10.33910/2686-9519-2022-14-4-570-593, http://zenodo.org/record/12815734 ...